Paternal preconception folate intake in relation to gestational age at delivery and birthweight of newborns conceived through assisted reproduction. Issue 5 (November 2019) - Martín-Calvo, Nerea; Mínguez-Alarcón, Lidia; Gaskins, Audrey J.; Nassan, Feiby L.; Williams, Paige L.; Souter, Irene; Hauser, Russ; Chavarro, Jorge E.; ,
ABSTRACT: Research question: Studies in rodents have shown that paternal folate intake prior to conception is associated with pregnancy and offspring outcomes. The aim of this study was to assess whether those associations might apply to humans as well. Design: Between 2007 and 2017, the study prospectively analysed data from 108 couples participating in a preconception cohort of couples undergoing fertility treatment using their own gametes, whose treatment resulted in 113 pregnancies during the course of the study. Paternal and maternal preconception folate intake was assessed using a validated food frequency questionnaire. Linear mixed models were used to assess whether paternal preconception folate intake was associated with gestational age at delivery and gestational age-specific birthweight, while accounting for correlated data and potential confounders. Results: In a multivariable-adjusted model, a 400 μg/day increase in preconception paternal folate intake was associated with a 2.6-day longer gestation (95% confidence interval 0.8–4.3) after adjusting for potential confounders, including maternal folate intake. Similar associations were found for folate from food and supplements. Maternal folate intake was not associated with gestational age at delivery. Neither paternal nor maternal folate intake was associated with gestational-age-specific birthweight. Conclusions: Higher paternal preconception folate intake was associated with slightly longer gestation among live births achieved through assisted reproduction. The results suggest that preconception exposures of the father may have an impact on the health of his offspring, and therefore that preconception care should shift from a woman-centric to a couple-based approach.